Two-photon dissociation of H2O and D2O at 266 nm - Atkins, C; Briggs, R; Halpern, J; Hancock, G (1989)
Polarisation of the fluorescence from A 2Σ+ OH and OD fragments of the two-photon dissociation of H2O and D2O at 266 nm is reported. Values of the alignment parameter A0(2) are found to be close to zero, independent of rotational level, in contrast to single-photon dissociation studies at slightly higher energies. The rotational energy distribution in OH(A 2Σ+) is very similar to those reported for single-photon dissociation. Laser-induced fluorescence of OH(X2Π) was observed, but was shown to arise from collisional processes and not from direct photolysis.